Orbital floor fracture with entrapment: Imaging and clinical correlations in 45 cases. (3rd September 2017) - Silverman, Nora; Spindle, Jordan; Tang, Sunny X.; Wu, Andrew; Hong, Bryan K.; Shore, John W.; Wester, Sara; Levin, Flora; Connor, Michael; Burt, Benjamin; Nakra, Tanuj; Shepler, Todd; et al.
ABSTRACT: Orbital floor fractures (OFF) with entrapment require prompt clinical and radiographic recognition for timely surgical correction. Correct CT radiographic interpretation of entrapped fractures can be subtle and thus missed. We reviewed the clinical, radiographic and intraoperative findings of 45 cases of entrapped OFF to correlate pre- and intraoperative findings with radiography. Retrospective review and statistical analysis of 45 patients with OFF using the chi squared and Kruskal–Wallis tests. Main outcome measures included patient demographics, clinical features, radiologic interpretation, intraoperative findings, and treatment outcomes. Twenty-one cases (47%) had radiologic evaluations of orbital CT scans that included commentary on possible entrapment. Intraoperatively, 16 (76%) of these patients had the inferior rectus muscle incarcerated in the fracture, while 5 (24%) patients had incarceration of the orbital fat. Possibility of entrapment was not commented on in the radiology reports of the remaining 24 (53%) cases. Intraoperatively, 13 (54%) of these patients had the inferior rectus muscle incarcerated in the fracture, while 11 (46%) patients had incarceration of the orbital fat. It is vital to assess the possibility of entrapment, especially in young patients, in the setting of OFF as a delay in diagnosis may lead to persistent diplopia, disfigurement, or bradycardia. Most radiology reports did not mention the possibility of entrapment in this cohort. A key concept is that entrapment occurs when any orbital tissue (muscle or fat) is trapped in the fracture site.